Portable composite electric pole material and preparation method thereof
By combining modified graphene oxide, composite modified fibers and modified glass fibers with epoxy resin, the problem of heavy and poor corrosion resistance of traditional telephone poles is solved, and the salt mist resistance of lightweight composite poles is significantly improved. Corrosion and mechanical properties extend service life.
Patent Information
- Application Number
- CN202411691597.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional steel bars and concrete poles have problems such as heavy weight, difficulty in construction and transportation and poor corrosion resistance. Especially in areas with severe salt spray corrosion, the existing composite poles have heavy quality and poor salt spray corrosion resistance. .
Modified graphene oxide, composite modified fiber, modified glass fiber and silane coupling agent KH-560 are combined with epoxy resin, and graphene oxide and glass fiber are modified by L-glutamic acid to form a lightweight type Composite pole material improves its dispersion and interface bonding in epoxy resin and enhances corrosion resistance.
It significantly improves the salt-alkali corrosion resistance, impact strength, tensile strength and bending strength of the composite material, extends the service life of the electric pole, and maintains better stability and mechanical properties in humid environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a lightweight composite pole material and a preparation method thereof. Background Art
[0002] In the field of power transmission and distribution, utility poles are important infrastructure, and their performance directly affects the safety and stability of the power grid. However, traditional steel and concrete utility poles have many shortcomings, such as heavy weight, difficult construction and transportation, and poor corrosion resistance, especially in areas with severe marine and salt spray corrosion. These problems are particularly prominent. Epoxy resin, as a multi-purpose, high-strength, and chemically resistant polymer, has become an ideal matrix for preparing composite pole materials. Its high strength and excellent adhesion enable epoxy resin to firmly combine with other materials after curing to form a composite material with excellent overall performance. At the same time, the chemical resistance, heat resistance, electrical insulation, low shrinkage, and low volatility of epoxy resin further enhance the corrosion resistance and stability of composite pole materials.
[0003] In order to further improve the mechanical properties of composite poles, modified fibers are selected as reinforcing materials. Modified fibers improve certain properties of conventional chemical fibers through chemical or physical methods. These modified fibers not only have excellent mechanical properties, but also can effectively resist corrosion and salt spray erosion, extending the service life of poles. Therefore, how to combine modified fibers and epoxy resin to prepare a material suitable for actual poles has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention
[0004] Technical issues solved In view of the above-mentioned shortcomings of the prior art, the present invention provides a lightweight composite pole material and a preparation method thereof, which can effectively solve the problems of heavy weight and poor salt spray corrosion resistance of the prior art pole materials.
[0005] Technical Solution To achieve the above objectives, the present invention is implemented through the following technical solutions: A lightweight composite pole material, the lightweight composite pole material is composed of the following components: modified graphene oxide, composite modified fiber, modified glass fiber, silane coupling agent KH-560 and epoxy resin; The modified graphene oxide is prepared by modifying graphene oxide with L-glutamic acid; The composite modified fiber is obtained by grafting polyurea nanofibers onto the surface of basalt fibers; The modified glass fiber is prepared by modifying the glass fiber with a silane coupling agent and oleic acid in sequence.
[0006] Furthermore, the preparation steps of the modified graphene oxide are: Step 2.1, weigh 1 g of graphene oxide and disperse it in 160 mL of deionized water, and obtain a graphene oxide dispersion after ultrasonic treatment, weigh 3 g of L-glutamic acid and dissolve it in 60 mL of sodium hydroxide solution, and the resultant after mechanical stirring and dispersion is recorded as L-glutamic acid dispersion; Step 2.2, pour the L-glutamic acid dispersion into the graphene oxide dispersion, stir and react for 24 hours under nitrogen protection after ultrasonic treatment, add 100 mL of anhydrous ethanol and 100 mL of deionized water after the reaction is completed, centrifuge and wash at a speed of 5000 r / min, and the obtained precipitate is the modified graphene oxide after drying.
[0007] Furthermore, the specific operation of ultrasonic treatment in step 2.1 is ultrasonic dispersion at a frequency of 28 kHz for 30 minutes, the concentration of the sodium hydroxide solution in step 2.1 is 4 mg / mL, the specific operation of mechanical stirring dispersion in step 2.1 is stirring at a speed of 500 r / min for 20 minutes, the specific operation of ultrasonic treatment in step 2.2 is ultrasonic dispersion at a frequency of 27 kHz for 20 minutes, the speed of stirring reaction in step 2.2 is 300 r / min, and the specific operation of drying treatment in step 2.2 is placed in a vacuum drying oven at 50°C and dried for 5-6 hours.
[0008] Furthermore, the preparation steps of the composite modified fiber are: Step 4.1, disperse 10g of chopped basalt fiber in 500mL of hydrochloric acid solution and stir evenly for 24h, then filter and remove the filtrate, pour the basalt fiber into 500mL of anhydrous ethanol for ultrasonic cleaning for 10min, filter and remove the filtrate, and then place in an oven at 50°C for drying for 2-3h, and the obtained fiber is recorded as etched fiber; Step 4.2, weigh 10.6 g of octadecylamine and 4 g of cyclohexylamine and dissolve them in 200 mL of anhydrous ethanol, add 10 g of etched fiber after ultrasonic dissolution and stir to react at 50°C, filter to remove the filtrate and add 200 mL of deionized water and continue stirring, the result is recorded as fiber suspension; Step 4.3, weigh 5.5g of diphenylmethane diisocyanate and dissolve it in 300mL of ethyl acetate to obtain a solution, then drop the solution into the fiber suspension, heat the fiber suspension during the dropping process until its temperature reaches 80°C, and let it stand at a constant temperature for 1h after the dropping is completed. Finally, filter and remove the filtrate, and dry it to obtain the composite modified fiber.
[0009] Furthermore, the mass fraction of the hydrochloric acid solution in step 4.1 is 5%, the rotation speed of the uniform stirring in step 4.1 is 400r / min, and the power of the ultrasonic cleaning in step 4.1 is 200w.
[0010] Furthermore, the specific operation of ultrasonic dissolution in step 4.2 is ultrasonic dispersion at a frequency of 26 kHz for 30 minutes, the specific operation of stirring reaction in step 4.2 is stirring at a speed of 300 r / min for 30 minutes, the specific operation of continued stirring in step 4.2 is stirring at a speed of 500 r / min for 10 minutes, the dripping rate in step 4.3 is 2 drops / s, and the specific operation of drying treatment in step 4.3 is placed in an oven at 50°C and dried for 2-3 hours.
[0011] Furthermore, the preparation steps of the modified glass fiber are: Step 7.1, weigh 5g of silane coupling agent KH-550 and dissolve it in 95g of 85% ethanol aqueous solution, add 20g of glass fiber after dissolution and dispersion, and immerse it in a water bath at 80°C for 8h, filter and remove the filtrate, and then dry it to obtain silane coupling agent modified glass fiber; Step 7.2, weigh 2g of silane coupling agent modified glass fiber and disperse it in 100mL of deionized water. Heat to 80°C under stirring and then drop 6mL of oleic acid. After keeping the temperature for 8h, remove the filtrate and rinse with deionized water for 3 times. After drying, the modified glass fiber is obtained.
[0012] Furthermore, the specific operation of dissolving and dispersing in step 7.1 is stirring at a speed of 500 r / min for 30 minutes, and the specific operation of drying in step 7.1 is drying in a vacuum drying oven at 1200° C. for 1 hour.
[0013] Furthermore, the stirring speed in step 7.2 is 200 r / min, the dripping rate in step 7.2 is 2 drops / s, and the specific operation of the drying treatment in step 7.2 is to place it in a vacuum drying oven at 50° C. and dry it for 2-3 hours.
[0014] A method for preparing a lightweight composite pole material, the method comprising the following steps: 3-5 parts by weight of modified graphene oxide, 1-2 parts by weight of composite modified fiber, 2-3 parts by weight of modified glass fiber and 2-3 parts by weight of silane coupling agent KH-560 are weighed and mixed, stirred at a speed of 500 r / min for 10 minutes and recorded as modified filler, 10-20 parts by weight of modified filler and 80-90 parts by weight of epoxy resin are weighed and poured into a torque rheometer for melt blending, and the result is a lightweight composite pole material.
[0015] Beneficial Effects The present invention provides a lightweight composite pole material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses L-glutamic acid to modify graphene oxide, which can prevent graphene oxide from agglomerating and improve the dispersibility of the modified graphene oxide in epoxy resin. Moreover, the modification of L-glutamic acid can also enhance the interfacial bonding force between graphene oxide and epoxy resin, so that graphene oxide is more evenly distributed in epoxy resin, further improving the overall performance of the prepared composite material. Secondly, graphene oxide itself has a large specific surface area and good barrier properties, which can effectively prevent the penetration of corrosive media (such as water, oxygen, etc.). After being modified with L-glutamic acid, the dispersibility of graphene oxide is improved, so that the barrier layer formed by it in epoxy resin is more dense and uniform, thereby further improving the anti-corrosion performance of the prepared composite material. Moreover, L-glutamic acid is a green corrosion inhibitor, and the amino and carboxyl groups in its molecules can form complexes with metal ions to reduce the activity of metal ions, thereby inhibiting the corrosion of metals. This corrosion inhibition combined with the barrier properties of graphene oxide can significantly improve the salt-alkali corrosion resistance of the composite material.
[0016] 2. The present invention utilizes addition polymerization to make polyurea nanofibers grow in situ on the surface of basalt fibers to prepare composite modified fibers. Adding them to epoxy resin can improve the wear resistance. During the friction process, polyurea nanofibers can effectively reduce the generation of wear particles and prevent them from further wearing the surface of the composite material. The load-bearing effect of basalt fibers can absorb the energy during the deformation of the material and further reduce the wear rate. Secondly, basalt fiber itself has high strength and modulus, and the addition of polyurea nanofibers can further enhance its mechanical properties. The composite modified fiber formed by the combination of the two can play a stronger reinforcing role in the composite material and improve the overall strength of the composite material. Furthermore, polyurea nanofibers have good corrosion resistance and can block the erosion of corrosive media to a certain extent. After combining them with basalt fibers, the composite modified fibers can form a denser anti-corrosion layer in the composite material, thereby improving the corrosion resistance of the composite material.
[0017] 3. The present invention sequentially modifies glass fiber with silane coupling agent and oleic acid and then adds the modified glass fiber to epoxy resin to prepare a composite material. The combined action of silane coupling agent and oleic acid can enhance the interfacial adhesion of glass fiber, so that glass fiber can better play its reinforcing role in the composite material and resist the damage of external force, thereby significantly improving the impact strength and tensile strength of the modified glass fiber reinforced epoxy resin composite material. Moreover, the improvement of interfacial adhesion also helps to improve the bending strength of the composite material, so that it can maintain better stability when subjected to bending load; secondly, the silane coupling agent can form a layer of hydrophilic silicon oxide film on the surface of the glass fiber, which can block the entry of external moisture, thereby improving the moisture and heat resistance of the composite material. In a humid environment, the composite material can maintain better stability and mechanical properties; finally, the firm combination of the silane coupling agent and the surface of the glass fiber can also form a layer of silicon oxide film with high hardness and wear resistance, which helps to improve the wear resistance of the composite material, extend its service life, and thereby enhance the durability of the prepared composite material. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention will be further described below in conjunction with the embodiments.
[0020] Example 1 A lightweight composite pole material of this embodiment, the lightweight composite pole material is composed of the following components: modified graphene oxide, composite modified fiber, modified glass fiber, silane coupling agent KH-560 and epoxy resin; The modified graphene oxide is prepared by modifying graphene oxide with L-glutamic acid. The preparation steps of the modified graphene oxide are as follows: Step 2.1, weigh 1 g of graphene oxide and disperse it in 160 mL of deionized water, and ultrasonically disperse it at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion, weigh 3 g of L-glutamic acid and dissolve it in 60 mL of a sodium hydroxide solution with a concentration of 4 mg / mL, and stir it at a speed of 500 r / min for 20 min to obtain the L-glutamic acid dispersion; Step 2.2, pour the L-glutamic acid dispersion into the graphene oxide dispersion, ultrasonically disperse at a frequency of 27 kHz for 20 minutes, and then stir and react at a speed of 300 r / min for 24 hours under nitrogen protection. After the reaction is completed, add 100 mL of anhydrous ethanol and 100 mL of deionized water and centrifuge and wash at a speed of 5000 r / min. The resulting precipitate is placed in a vacuum drying oven at 50°C and dried for 5 hours to obtain the modified graphene oxide.
[0021] The composite modified fiber is prepared by grafting polyurea nanofibers onto the surface of basalt fiber. The preparation steps of the composite modified fiber are as follows: Step 4.1, 10 g of chopped basalt fiber was dispersed in 500 mL of 5% hydrochloric acid solution and stirred evenly at a speed of 400 r / min for 24 h, then the filtrate was filtered out and the basalt fiber was poured into 500 mL of anhydrous ethanol and ultrasonically cleaned at a power of 200 W for 10 min, the filtrate was filtered out and then placed in an oven at 50°C for 2 h to be dried, and the obtained fiber was recorded as the etched fiber; Step 4.2, weigh 10.6 g of octadecylamine and 4 g of cyclohexylamine and dissolve them in 200 mL of anhydrous ethanol, add 10 g of etched fiber and stir at 300 r / min for 30 min at 50°C, filter and remove the filtrate, add 200 mL of deionized water and stir at 500 r / min for 10 min, the result is recorded as fiber suspension; Step 4.3, weigh 5.5g of diphenylmethane diisocyanate and dissolve it in 300mL of ethyl acetate to obtain a dissolving solution, then drip the dissolving solution into the fiber suspension at a dripping rate of 2 drops / s, heat the fiber suspension during the dripping process until its temperature reaches 80°C, and let it stand at a constant temperature for 1h after the dripping is completed. Finally, filter out the filtrate and dry the precipitate in an oven at 50°C for 2h to obtain the composite modified fiber.
[0022] The modified glass fiber is prepared by modifying the glass fiber with a silane coupling agent and oleic acid in sequence. The preparation steps of the modified glass fiber are as follows: Step 7.1, weigh 5 g of silane coupling agent KH-550 and dissolve it in 95 g of 85% ethanol aqueous solution, stir at a speed of 500 r / min for 30 min, add 20 g of glass fiber and immerse it in a water bath at 80° C. for 8 h, filter out the filtrate and dry it in a vacuum drying oven at 1200° C. for 1 h to obtain silane coupling agent modified glass fiber; Step 7.2, weigh 2g of silane coupling agent modified glass fiber and disperse it in 100mL of deionized water. Heat to 80°C with stirring at a speed of 200r / min, then add 6mL of oleic acid at a rate of 2 drops / s. After keeping the reaction for 8h, remove the filtrate and rinse with deionized water 3 times. Place it in a vacuum drying oven at 50°C and dry it for 2h to obtain the modified glass fiber.
[0023] A method for preparing a lightweight composite pole material, the preparation method comprising the following steps: Weigh 3 parts by weight of modified graphene oxide, 1 part by weight of composite modified fiber, 2 parts by weight of modified glass fiber and 2 parts by weight of silane coupling agent KH-560, mix them, stir them at a speed of 500 r / min for 10 min, and record them as modified filler. Weigh 10 parts by weight of modified filler and 80 parts by weight of epoxy resin, pour them into a torque rheometer for melt blending, and the result is a lightweight composite pole material.
[0024] Example 2 A lightweight composite pole material of this embodiment, the lightweight composite pole material is composed of the following components: modified graphene oxide, composite modified fiber, modified glass fiber, silane coupling agent KH-560 and epoxy resin; The modified graphene oxide is prepared by modifying graphene oxide with L-glutamic acid. The preparation steps of the modified graphene oxide are as follows: Step 2.1, weigh 1 g of graphene oxide and disperse it in 160 mL of deionized water, and ultrasonically disperse it at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion, weigh 3 g of L-glutamic acid and dissolve it in 60 mL of a sodium hydroxide solution with a concentration of 4 mg / mL, and stir it at a speed of 500 r / min for 20 min to obtain the L-glutamic acid dispersion; Step 2.2, pour the L-glutamic acid dispersion into the graphene oxide dispersion, ultrasonically disperse at a frequency of 27 kHz for 20 minutes, and then stir and react at a speed of 300 r / min for 24 hours under nitrogen protection. After the reaction is completed, add 100 mL of anhydrous ethanol and 100 mL of deionized water and centrifuge and wash at a speed of 5000 r / min. The resulting precipitate is placed in a vacuum drying oven at 50°C and dried for 6 hours to obtain the modified graphene oxide.
[0025] The composite modified fiber is prepared by grafting polyurea nanofibers onto the surface of basalt fiber. The preparation steps of the composite modified fiber are as follows: Step 4.1, 10 g of chopped basalt fiber was dispersed in 500 mL of 5% hydrochloric acid solution and stirred evenly at a speed of 400 r / min for 24 h, then the filtrate was filtered out and the basalt fiber was poured into 500 mL of anhydrous ethanol and ultrasonically cleaned at a power of 200 w for 10 min, the filtrate was filtered out and then placed in an oven at 50°C for 3 h to be dried, and the obtained fiber was recorded as the etched fiber; Step 4.2, weigh 10.6 g of octadecylamine and 4 g of cyclohexylamine and dissolve them in 200 mL of anhydrous ethanol, add 10 g of etched fiber and stir at 300 r / min for 30 min at 50°C, filter and remove the filtrate, add 200 mL of deionized water and stir at 500 r / min for 10 min, the result is recorded as fiber suspension; Step 4.3, weigh 5.5g of diphenylmethane diisocyanate and dissolve it in 300mL of ethyl acetate to obtain a dissolving solution, then drip the dissolving solution into the fiber suspension at a dripping rate of 2 drops / s, heat the fiber suspension during the dripping process until its temperature reaches 80°C, and let it stand at a constant temperature for 1h after the dripping is completed. Finally, filter out the filtrate and place the precipitate in an oven at 50°C to dry for 3h to obtain the composite modified fiber.
[0026] The modified glass fiber is prepared by modifying the glass fiber with a silane coupling agent and oleic acid in sequence. The preparation steps of the modified glass fiber are as follows: Step 7.1, weigh 5 g of silane coupling agent KH-550 and dissolve it in 95 g of 85% ethanol aqueous solution, stir at a speed of 500 r / min for 30 min, add 20 g of glass fiber and immerse it in a water bath at 80° C. for 8 h, filter out the filtrate and dry it in a vacuum drying oven at 1200° C. for 1 h to obtain silane coupling agent modified glass fiber; Step 7.2, weigh 2g of silane coupling agent modified glass fiber and disperse it in 100mL of deionized water. Heat to 80°C with stirring at a speed of 200r / min, then add 6mL of oleic acid at a rate of 2 drops / s. After keeping the reaction for 8h, remove the filtrate and rinse with deionized water 3 times. Place it in a vacuum drying oven at 50°C and dry it for 3h to obtain the modified glass fiber.
[0027] A method for preparing a lightweight composite pole material, the preparation method comprising the following steps: Weigh 5 parts by weight of modified graphene oxide, 2 parts by weight of composite modified fiber, 3 parts by weight of modified glass fiber and 3 parts by weight of silane coupling agent KH-560, mix them, stir them at a speed of 500 r / min for 10 min and record them as modified filler. Weigh 20 parts by weight of modified filler and 90 parts by weight of epoxy resin, pour them into a torque rheometer for melt blending, and the result is a lightweight composite pole material.
[0028] Example 3 A lightweight composite pole material of this embodiment, the lightweight composite pole material is composed of the following components: modified graphene oxide, composite modified fiber, modified glass fiber, silane coupling agent KH-560 and epoxy resin; The modified graphene oxide is prepared by modifying graphene oxide with L-glutamic acid. The preparation steps of the modified graphene oxide are as follows: Step 2.1, weigh 1 g of graphene oxide and disperse it in 160 mL of deionized water, and ultrasonically disperse it at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion, weigh 3 g of L-glutamic acid and dissolve it in 60 mL of a sodium hydroxide solution with a concentration of 4 mg / mL, and stir it at a speed of 500 r / min for 20 min to obtain the L-glutamic acid dispersion; Step 2.2, pour the L-glutamic acid dispersion into the graphene oxide dispersion, ultrasonically disperse at a frequency of 27 kHz for 20 minutes, and then stir and react at a speed of 300 r / min for 24 hours under nitrogen protection. After the reaction is completed, add 100 mL of anhydrous ethanol and 100 mL of deionized water and centrifuge and wash at a speed of 5000 r / min. The resulting precipitate is placed in a vacuum drying oven at 50°C and dried for 6 hours to obtain the modified graphene oxide.
[0029] The composite modified fiber is prepared by grafting polyurea nanofibers onto the surface of basalt fiber. The preparation steps of the composite modified fiber are as follows: Step 4.1, 10 g of chopped basalt fiber was dispersed in 500 mL of 5% hydrochloric acid solution and stirred evenly at a speed of 400 r / min for 24 h, then the filtrate was filtered out and the basalt fiber was poured into 500 mL of anhydrous ethanol and ultrasonically cleaned at a power of 200 W for 10 min, the filtrate was filtered out and then placed in an oven at 50°C for 2 h to be dried, and the obtained fiber was recorded as the etched fiber; Step 4.2, weigh 10.6 g of octadecylamine and 4 g of cyclohexylamine and dissolve them in 200 mL of anhydrous ethanol, add 10 g of etched fiber and stir at 300 r / min for 30 min at 50°C, filter and remove the filtrate, add 200 mL of deionized water and stir at 500 r / min for 10 min, the result is recorded as fiber suspension; Step 4.3, weigh 5.5g of diphenylmethane diisocyanate and dissolve it in 300mL of ethyl acetate to obtain a dissolving solution, then drip the dissolving solution into the fiber suspension at a dripping rate of 2 drops / s, heat the fiber suspension during the dripping process until its temperature reaches 80°C, and let it stand at a constant temperature for 1h after the dripping is completed. Finally, filter out the filtrate and place the precipitate in an oven at 50°C to dry for 3h to obtain the composite modified fiber.
[0030] The modified glass fiber is prepared by modifying the glass fiber with a silane coupling agent and oleic acid in sequence. The preparation steps of the modified glass fiber are as follows: Step 7.1, weigh 5 g of silane coupling agent KH-550 and dissolve it in 95 g of 85% ethanol aqueous solution, stir at a speed of 500 r / min for 30 min, add 20 g of glass fiber and immerse it in a water bath at 80° C. for 8 h, filter out the filtrate and dry it in a vacuum drying oven at 1200° C. for 1 h to obtain silane coupling agent modified glass fiber; Step 7.2, weigh 2g of silane coupling agent modified glass fiber and disperse it in 100mL of deionized water. Heat to 80°C with stirring at a speed of 200r / min, then add 6mL of oleic acid at a rate of 2 drops / s. After keeping the reaction for 8h, remove the filtrate and rinse with deionized water 3 times. Place it in a vacuum drying oven at 50°C and dry it for 3h to obtain the modified glass fiber.
[0031] A method for preparing a lightweight composite pole material, the preparation method comprising the following steps: Weigh 4 parts by weight of modified graphene oxide, 2 parts by weight of composite modified fiber, 3 parts by weight of modified glass fiber and 2 parts by weight of silane coupling agent KH-560, mix them, stir them at a speed of 500 r / min for 10 min and record them as modified filler. Weigh 15 parts by weight of modified filler and 85 parts by weight of epoxy resin, pour them into a torque rheometer for melt blending, and the result is a lightweight composite pole material.
[0032] Comparative Example 1 The lightweight composite pole material and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the modified graphene oxide in Example 1 is replaced with unmodified graphene oxide.
[0033] Comparative Example 2 The lightweight composite pole material and preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the composite modified fiber in Example 1 is replaced with unmodified basalt fiber.
[0034] Comparative Example 3 The lightweight composite pole material and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified glass fiber in Example 1 is replaced with unmodified glass fiber.
[0035] Performance Testing The lightweight composite pole materials prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows: 1. According to the mechanical testing standards of GB / T1040-2006 and GB / T9341-2008, the bending strength and tensile strength of Examples 1-3 and Comparative Examples 1-3 were tested, and the obtained data are recorded in the following table; 2. The impact strength of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T1043-2008, and the obtained data are recorded in the following table; 3. The salt spray resistance of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard test of GB / T1771-1991, and the obtained data are recorded in the following table;
[0036] It can be seen from the data in the above table that the mechanical properties of the lightweight composite pole materials in Examples 1-3 are significantly better than those in Comparative Examples 2-3, indicating that adding composite modified fibers and modified glass fibers to the lightweight composite pole materials can significantly improve the mechanical properties and mechanical properties; secondly, the salt spray resistance time of the lightweight composite pole materials in Examples 1-3 is significantly higher than that in Comparative Example 1, indicating that the addition of modified graphene oxide can significantly improve the salt spray corrosion resistance of the lightweight composite pole materials.
[0037] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lightweight composite pole material, characterized in that: The lightweight composite pole material is composed of the following components: modified graphene oxide, composite modified fiber, modified glass fiber, silane coupling agent KH-560 and epoxy resin; The modified graphene oxide is prepared by modifying graphene oxide with L-glutamic acid; The composite modified fiber is obtained by grafting polyurea nanofibers onto the surface of basalt fibers; The modified glass fiber is prepared by modifying the glass fiber with a silane coupling agent and oleic acid in sequence.
2. A lightweight composite pole material according to claim 1, characterized in that: The preparation steps of the modified graphene oxide are: Step 2.1, weigh 1 g of graphene oxide and disperse it in 160 mL of deionized water, and obtain a graphene oxide dispersion after ultrasonic treatment, weigh 3 g of L-glutamic acid and dissolve it in 60 mL of sodium hydroxide solution, and the resultant after mechanical stirring and dispersion is recorded as L-glutamic acid dispersion; Step 2.2, pour the L-glutamic acid dispersion into the graphene oxide dispersion, stir and react for 24 hours under nitrogen protection after ultrasonic treatment, add 100 mL of anhydrous ethanol and 100 mL of deionized water after the reaction is completed, centrifuge and wash at a speed of 5000 r / min, and the obtained precipitate is the modified graphene oxide after drying.
3. A lightweight composite pole material according to claim 2, characterized in that: The specific operation of ultrasonic treatment in step 2.1 is ultrasonic dispersion at a frequency of 28 kHz for 30 minutes, the concentration of the sodium hydroxide solution in step 2.1 is 4 mg / mL, the specific operation of mechanical stirring dispersion in step 2.1 is stirring at a speed of 500 r / min for 20 minutes, the specific operation of ultrasonic treatment in step 2.2 is ultrasonic dispersion at a frequency of 27 kHz for 20 minutes, the speed of stirring reaction in step 2.2 is 300 r / min, and the specific operation of drying treatment in step 2.2 is placed in a vacuum drying oven at 50°C and dried for 5-6 hours.
4. The lightweight composite pole material according to claim 1, characterized in that: The preparation steps of the composite modified fiber are: Step 4.1, disperse 10g of chopped basalt fiber in 500mL of hydrochloric acid solution and stir evenly for 24h, then filter and remove the filtrate, pour the basalt fiber into 500mL of anhydrous ethanol for ultrasonic cleaning for 10min, filter and remove the filtrate, and then place in an oven at 50°C for drying for 2-3h, and the obtained fiber is recorded as etched fiber; Step 4.2, weigh 10.6 g of octadecylamine and 4 g of cyclohexylamine and dissolve them in 200 mL of anhydrous ethanol, add 10 g of etched fiber after ultrasonic dissolution and stir to react at 50°C, filter to remove the filtrate and add 200 mL of deionized water and continue stirring, the result is recorded as fiber suspension; Step 4.3, weigh 5.5g of diphenylmethane diisocyanate and dissolve it in 300mL of ethyl acetate to obtain a solution, then drop the solution into the fiber suspension, heat the fiber suspension during the dropping process until its temperature reaches 80°C, and let it stand at a constant temperature for 1h after the dropping is completed. Finally, filter and remove the filtrate, and dry it to obtain the composite modified fiber.
5. The lightweight composite pole material according to claim 4, characterized in that: The mass fraction of the hydrochloric acid solution in step 4.1 is 5%, the rotation speed of the uniform stirring in step 4.1 is 400r / min, and the power of the ultrasonic cleaning in step 4.1 is 200w.
6. The lightweight composite pole material according to claim 4, characterized in that: The specific operation of ultrasonic dissolution in step 4.2 is ultrasonic dispersion at a frequency of 26 kHz for 30 minutes, the specific operation of stirring reaction in step 4.2 is stirring at a speed of 300 r / min for 30 minutes, the specific operation of continued stirring in step 4.2 is stirring at a speed of 500 r / min for 10 minutes, the dripping rate in step 4.3 is 2 drops / s, and the specific operation of drying treatment in step 4.3 is placed in an oven at 50°C and dried for 2-3 hours.
7. The lightweight composite pole material according to claim 1, characterized in that: The preparation steps of the modified glass fiber are: Step 7.1, weigh 5g of silane coupling agent KH-550 and dissolve it in 95g of 85% ethanol aqueous solution, add 20g of glass fiber after dissolution and dispersion, and immerse it in a water bath at 80°C for 8h, filter and remove the filtrate, and then dry it to obtain silane coupling agent modified glass fiber; Step 7.2, weigh 2g of silane coupling agent modified glass fiber and disperse it in 100mL of deionized water. Heat to 80°C under stirring and then drop 6mL of oleic acid. After keeping the temperature for 8h, remove the filtrate and rinse with deionized water for 3 times. After drying, the modified glass fiber is obtained.
8. The lightweight composite pole material according to claim 7, characterized in that: The specific operation of dissolving and dispersing in step 7.1 is stirring at a speed of 500 r / min for 30 minutes, and the specific operation of drying in step 7.1 is drying in a vacuum drying oven at 1200° C. for 1 hour.
9. The lightweight composite pole material according to claim 7, characterized in that: The stirring speed in step 7.2 is 200 r / min, the dripping rate in step 7.2 is 2 drops / s, and the specific operation of the drying treatment in step 7.2 is to place it in a vacuum drying oven at 50° C. and dry it for 2-3 hours.
10. A method for preparing a lightweight composite pole material according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: 3-5 parts by weight of modified graphene oxide, 1-2 parts by weight of composite modified fiber, 2-3 parts by weight of modified glass fiber and 2-3 parts by weight of silane coupling agent KH-560 are weighed and mixed, stirred at a speed of 500 r / min for 10 minutes and recorded as modified filler, 10-20 parts by weight of modified filler and 80-90 parts by weight of epoxy resin are weighed and poured into a torque rheometer for melt blending, and the result is a lightweight composite pole material.
Citation Information
Patent Citations
Manufacturing method of high-voltage composite material double-loop single-pole transmission tower
CN102041919A
Basalt fiber lightweight muck truck carriage
CN116252819A
Anti-corrosion material-coated discrete graphene sheets and Anti-corrosion coating composition containing same
US20190345344A1
Anti-corrosion coating composition
US20200010695A1
Cited By
Corrosion-resistant oil casing material and preparation method thereof
CN120904749A
